Catalytic activation of esterases by PEGylation for polyester synthesis - Noro, Jennifer (2019)
In this work we explored PEGylation as an efficient strategy to improve esterases catalytic performance. For this, we PEGylated three esterases, namely lipase from Candida antarctica B (CALB), lipase from Thermomyces lanuginosus (TL) and cutinase from Fusarium solani pisi (CUT) and evaluated their catalytic performance by using the biosynthesis of poly(ethylene glutarate) as model reaction. After PEGylation with a 5 kDa aldehydePEG, CALB and cutinase revealed an increase of activity against pnitrophenyl butyrate hydrolysis (2fold of increase for CALB and 4fold of increase for cutinase). Unmodified and PEGylated lipase TL displayed however similar activity results. The polymerase activity of native and PEGylated esterases was also assessed. The data revealed a higher polymerase activity for the lipase TL and cutinase PEGylated forms (88 % conversion for PEGlipase TL and 34 % for PEGcutinase). Molecular dynamics were used to evaluate the effect of PEG on the geometry of the active site of enzymes with lid domain (TL and CALB). These studies corroborate the experimental data revealing a more open active site cavity for the PEGylated catalysts facilitating the catalysis.